In silico screening of potential bioactive peptides from spent Arabica coffee (Coffea Arabica) beans storage proteins - Clarito, Bernadette L. (College of Home Economics, University of the Philippines Diliman, 2023)
Spent coffee grounds (SCG) constitute the majority of coffee by-products. They usually end up in landfills due to their lack of economic value but the remaining amount of proteins in SCG can still be used in producing bioactive peptides which suggests its potential utilization in food science and nutrition. This study investigated the potential of different storage proteins found in Coffea arabica as a source of bioactive peptides through an in-silico analysis and simulated enzymatic hydrolysis. The enzymes utilized for the hydrolysis were plant proteases to evaluate its potential in commercially preparing protein hydrolysates with biological activities, and digestive enzymes to partially assess the possibility of SCG as a functional ingredient. Results show that DPP-IV and ACE inhibitors were the most dominant activities for all the protein hydrolysates regardless of the enzymes used in hydrolysis. With digestive enzymes, Patatin showed the highest potential in DPP-IV inhibitory, antioxidative, and antibacterial activities, while 11S Globulin exhibited the highest potential in ACE inhibitory activity. Using plant proteases, Glutelin Type-A 2-like had the best potential in producing protein hydrolysates with multiple biological activities including ACE inhibitory, anti-inflammatory, antioxidative, and DPP-IV inhibitory activities. It is important to note that this study may contain generalized results as the in-silico tools utilized may not be able to capture certain factors affecting enzymatic hydrolyses. Thus, the study is only meant to serve as a preliminary screening for the bioactivity profile of SCG proteins, and more empirical data is needed for a more comprehensive understanding of the proteins studied.